The Theoretical Background of the Relations Between Police Presence and Public Safety - Papp, Dávid (Magyar Rendészet, 2025)
Based on the lessons of the Kansas City experiment in the early 1970s and the Minneapolis experiment in 1998, it can be said that organising public presence on the basis of professional skills and local characteristics significantly reduces crime and improves public safety. The aim of the study is to examine and present the theoretical background of the research topic by integrating and systematising the theories and conceptual definitions related to the two major areas. Understanding the theoretical foundations and previous scientific findings is essential for measuring the relationships, changes, and correlations between the factors. The descriptive work is based on the method of document analysis. In presenting the theoretical framework and the results of certain previous, significant empirical researches, it is important to clarify the concepts, functions and individual characteristics of the various factors and phenomena, followed by an examination of their interrelations. As a result of the study, it can be concluded that public safety is an extremely complex phenomenon influenced by numerous factors beyond police activities. Furthermore, due to the availability of the necessary data, it is worth examining the relationship and potential co-variation between police presence and public safety, through empirical research. The previous empirical research findings, theoretical foundations on this topic can undoubtedly contribute to advancing the effectiveness and efficiency of practical service planning, organisation, and delivery. The most important conclusion can be drawn based on the results is that the improving public safety is not only the result of the police presence. The current trends in crime and the impression of people are also determined by other factors. In connection with future research, it may be interesting to examine the issue at the local (police station) level, as well as the changes of number of specific police measures and certain crimes in public areas.